Proteomic Perspective of Cadmium Tolerance in Providencia rettgeri Strain KDM3 and Its In-situ Bioremediation Potential in Rice Ecosystem - Salaskar, Darshana A.; Padwal, Mahesh K.; Gupta, Alka; Basu, Bhakti; Kale, Sharad P. (Frontiers in Microbiology, 2022)
In this study, a multi-metal-tolerant natural bacterial isolate Providencia rettgeri strain KDM3 from an industrial effluent in Mumbai, India, showed high cadmium (Cd) tolerance. Providencia rettgeri grew in the presence of more than 100 ppm (880 μM) Cd (LD50 = 100 ppm) and accumulated Cd intracellularly. Following Cd exposure, a comparative proteome analysis revealed molecular mechanisms underlying Cd tolerance. Among a total of 69 differentially expressed proteins (DEPs) in Cd-exposed cells, de novo induction of ahpCF operon proteins and L-cysteine/L-cystine shuttle protein FliY was observed, while Dps and superoxide dismutase proteins were overexpressed, indicating upregulation of a robust oxidative stress defense. ENTRA1, a membrane transporter showing homology to heavy metal transporter, was also induced de novo. In addition, the protein disaggregation chaperone ClpB, trigger factor, and protease HslU were also overexpressed. Notably, 46 proteins from the major functional category of energy metabolism were found to be downregulated. Furthermore, the addition of P. rettgeri to Cd-spiked soil resulted in a significant reduction in the Cd content [roots (11%), shoot (50%), and grains (46%)] of the rice plants. Cd bioaccumulation of P. rettgeri improved plant growth and grain yield. We conclude that P. rettgeri, a highly Cd-tolerant bacterium, is an ideal candidate for in-situ bioremediation of Cd-contaminated agricultural soils.